PERANCANGAN PERANGKAT LUNAK PENGENALAN POLA KARAKTER MENGGUNAKAN JARINGAN SYARAF TIRUAN PERCEPTRON - David David (SISFOTENIKA, 2011)
Abstracts: Artificial Neural Net is a method in soft computing that imitate the structure of biological nervous, where multiple nodes communicate with each other through synapses that interconnect them. That method can be utilized for pattern recognition processes, such as hand writing character recognition. This paper is aimed to develop hand writing character recognition using Artificial Neural Net method. Perceptron neural network is adopted in Artificial Neural Net. A mapping method is used for preprocessing to segment a character image to be processed by Artificial Neural Net. The experimental results show that among all of successful segmented characters of all the training data. the system recognizes the characters with an accuracy close to 79,2%.Keywords: Character Recognition, Artificial Neural Net, Image Processing,Perceptron